Planning and Organization of Vocational School Activities with Google Calendar at Asysyakirin Tangerang Islamic High School - Irfan Nurdiansyah; Ari Hidayatullah (CV. Aksara Global Akademia, 2024)
Community service Planning and Organization of Vocational School Activities with Google Calendar focuses on how to use the features in Google Calendar from the initial stages to the results achieved. The aim of this service is to improve the performance of structured activities or meetings with digitalization.